PRE-SERVICE TEACHERS’ ATTITUDES TOWARDS ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Maizyurah, Maizyurah; Yasim, Sukmawati; Danial, Muhammad (English Language, Linguistics, and Culture International Journal, 2021)
The purpose of this research is to find (1) pre-service teachers' attitudes towards online learning during the covid-19 pandemic. (2) pre-service teachers' difficulties towards online learning during the covid-19 pandemic. This study uses a qualitative method and also the design this research employed descriptive design. The participants of this study were students of English Education class B, second semester of class 2020 at the University of West Sulawesi, who were selected using a purposive sampling technique. The data of this study were obtained by using observation, questionnaires and interviews. The data obtained were then analyzed into three main phases, namely data collection, data display, data condensation and drawing conclusions. The results of this study indicate that (1) there are three components of students' attitudes towards the use of online learning during the COVID-19 pandemic, namely the cognitive component, affective component, and conative component, (2) there are several difficulties that students encounter during the online learning process during the Covid-19 pandemic namely inadequate internet network connections in several student areas, lack of student learning facilities such as internet quota, books and laptops, and limited storage on student cellphones to store learning files provided by lecturers. This shows that students feel safe and comfortable in reducing and eradicating the spread of the covid-19 virus, students know various online learning media and the learning process can be done anywhere and anytime. However, there are many things that become obstacles for students during the online learning process, it is possible that this is the reason some students cannot participate and be active in carrying out the online learning process during the pandemic.